DESAIN PENATAAN PENGEMBANGAN TAMAN WISATA SANGRAJA SEBAGAI SARANA PENINGKATAN KAWASAN WISATA DI MAJALENGKA - WAWANG NURDAYAMAN; ATIE ERNAWATI; RITA LAKSMITASARI (Faktor Exacta, 2013)
.Wilayah Majalengka is currently conducting development and the development potential of the region as a whole in all areas. Natural wealth is one of the potential areas that are very appealing to the interests of the development of the tourism sector in Majalengka. In line with government policy, the development of Tourism Sangraja Park neighborhood is one of the assets that make the Park tour Tourism Sangraja as a center / central Majalengka tourist district. Future is expected to be the center of tourist activities and tourist information centers that can generate tourism potential to be around the district Majalengka. To that required research, analysis and planning Sangraja Travel Park area so that it will manifest a tourist area that according to the expectations and needs of the community. Elements that exist in the design area is Taman Wisata Sangraja recreation / entertainment in which there are elements of education and culture, sports and business elements of which are contained in the provision of tourist facilities that include: Travel Tirta (Forum for Air Travel), Culinary Tourism Zone and Art Market, Campgrounds, Forum Games Natural, Specialty, Arena Fitness, Building Supply Rental, Central Provision of Travel Information Majalengka. With the realization Sangraja Tourism Park is expected to provide a positive role in the development of the tourism sector in particular and development in general Majalengka district, so as to promote the development of the economic sector, can also raise local revenue tarap local community life through the absorption of new jobs and provide opportunities in the provision of services tourism as well as a continuity of tourism activities that Parks Tourism Sangraja become the center of attraction and attraction that support district development Majalengka in current and future. Keywords: Garden Tour, Sangraja, Majalengka Area Tourism and Travel